Popularity of the metaverse: Embodied social presence theory perspective - Zhang, Guihua; Cao, Junwei; Liu, Dong; Qi, Jie (Frontiers in Psychology, 2022)
Abstract: With Facebook's name changing to Meta, the metaverse concept has become popular again. There are many indications that the current fashionableness of the metaverse is not driven by technical factors, rather related to the public hype. To clarify the reasons for the increasing popularity of the concept, this study develops a model based on embodied social presence theory. We surveyed 292 metaverse users, and analyzed the obtained data using partial least squares structural equation modeling (PLS-SEM). The results show that the main technical factors influencing the metaverse popularity do not significantly predict users' embodied presence and embodied co-presence, while users' imagination positively predicts their embodied presence in the metaverse and positively influences users' willingness to continuously participate through the multiple mediating effects of embodied presence and co-presence. The results of this study confirm, to some extent, that user imagination triggered by public opinion drives the popularity of the metaverse.